2023
DOI: 10.3390/land12020415
|View full text |Cite
|
Sign up to set email alerts
|

A Decision Support Tool for Green Infrastructure Planning in the Face of Rapid Urbanization

Abstract: Multifunctional green infrastructure, a key component of compact sustainable cities, is challenged by the pressures associated with rapid urbanization. In this paper, we present a method that uses remote sensing, GIS modeling and stakeholder engagement to produce a decision support tool that communicates the availability and need for green infrastructure benefits. The case study presented is the City of Tshwane, South Africa, a Global South city facing rapid urbanization. We found that this method of mapping g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…The authors of the study (Mudzengi et al, 2021) discuss the existing methods used in urban planning, which entail addressing the fast expansion of informal settlements, engaging local people, and prioritizing urban sustainability and resilience. The article also addresses particular obstacles encountered in urban planning in Africa, such as the fast increase in urban population, the management of informal settlements, restricted financial resources, urban governance, and socio-economic disparities (Brom et al, 2023). Urban planning in Africa provides several socio-economic advantages, including enhanced quality of life, employment generation, encouragement of economic growth, greater access to essential services, and promotion of sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the study (Mudzengi et al, 2021) discuss the existing methods used in urban planning, which entail addressing the fast expansion of informal settlements, engaging local people, and prioritizing urban sustainability and resilience. The article also addresses particular obstacles encountered in urban planning in Africa, such as the fast increase in urban population, the management of informal settlements, restricted financial resources, urban governance, and socio-economic disparities (Brom et al, 2023). Urban planning in Africa provides several socio-economic advantages, including enhanced quality of life, employment generation, encouragement of economic growth, greater access to essential services, and promotion of sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Urban planning in Africa faces major challenges related to rapid population growth and changing political and economic dynamics (Brom et al, 2023). This growth necessitates rapid adaptation of planning strategies, but many municipalities in Africa face financial constraints, making it difficult to mobilize long-term funding (Thorn et al, 2021).…”
Section: Specific Challenges Of Urban Planning In the African Contextmentioning
confidence: 99%
“…with the help of AI tools using image-based species recognition functionality on mobile applications [41]. The ML algorithms (artificial neural network, probabilistic neural network, convolutional neural network, or other combinations of technologies [5]) assist field inspectors during the GBI inventory process. Better accuracy has been obtained when trained models use object datasets and libraries located geographically.…”
Section: Gbi Operation and Maintenancementioning
confidence: 99%
“…Research over time in the field of GBI has identified several representative gaps, which a DSS should be able to address. For example, GBI and DDS has been identified in [5] as a solution to rapid urbanization. The proposed DSS architecture solutions for GBI may face institutional and governance challenges such as unclear responsibilities, limited resources, and conflicting policies.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of Geographic Information Systems (GIS) enables the identification of priority areas for strategically placing and leveraging GI [30,33]. This analytical approach assumes paramount importance in enabling urban planners to make informed decisions regarding GI, fostering sustainable urban development [34,35]. However, existing research with limited exploration into the evaluation of GI's suitability [31] is often confined to small-scale analyses and sparse investigations at the broader city or community scales [1].…”
Section: Introductionmentioning
confidence: 99%